Meta-Analysis: The Validity of Using Flipbook Learning Media in Education: Penelitian - Erma Nengsih; Rahmawati Darussyamsu (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Learning innovation 4.0 encourages the use of interactive digital media such as flipbooks to increase motivation and learning outcomes. A flipbook is a multimedia e-book that contains text, images, videos, and animations that resemble a printed book. Validity by subject matter and media experts is important to ensure the suitability of the content and functionality of the flipbook media before use. The data collection method used was meta-analysis. The data collection technique was carried out by searching a number of relevant and reliable journals. There were 10 articles used as samples, which discussed the development of flipbooks or the validity of flipbooks. The data obtained from this meta-analysis became a reference in this study. Based on the meta-analysis, there were three components, namely content, language, and presentation. The average percentage obtained from these three components was very high. The average of these components is 90.29% for content validity, 89.27% for language validity, and 91.18% for presentation validity. In general, the results of content, language, and presentation validity fall into the category of highly valid. Thus, based on the validity analysis results, flipbooks can be declared a highly valid product for application in learning activities.